Thực trạng văn hoá chất lượng ở các trường trung học phổ thông công lập tại phường Bình Phú, thành phố Hồ Chí Minh - Vũ Thị Thu Trang, Vũ Thị Thu Trang; Trần Văn Trung, Trần Văn Trung; Đỗ Đình Thái, Đỗ Đình Thái (Tạp chí Giáo dục, 2026)
In the process of fundamental and comprehensive educational reform in Vietnam, a culture of quality is increasingly seen as the foundation for shaping a modern, transparent, and sustainable educational environment. In Binh Phu Ward, Ho Chi Minh City - a newly reorganized area resulting from administrative boundary mergers - the need to strengthen and improve school quality is critical. Building a culture of quality not only contributes to creating a positive, democratic learning environment and to forming organizational identity, but also enhances prestige and strengthens social trust in educational institutions. This article presents the current state of quality culture in public high schools in Binh Phu Ward, based on feedback from 154 administrators and teachers at two schools. The survey results show that the quality culture in these institutions has been established relatively stably and operates effectively, with an overall rating of "Fair" to "Good". However, specific differences still exist among schools regarding the extent of dissemination and consistency in implementation. The above results contribute to objectively describing the current state of quality culture in the research area, thereby providing a valuable reference for the management and development of educational quality in high schools in the present period.